Diversidade genética entre genótipos de cajueiro (Anacardium occidentale L.) e qualidade do fruto e pseudofruto - Lucena, Vanja Maria Xaud (2006)
Work was carried out, regarding the classification of the genetic and phenotypical variation and the genetic constitution of cashew trees (Anacardium occidentale L.). Research was done to find the quality of its fruits and pseudofruits by morphological and physio-chemical analization during the years 2005 and 2006, as well as an analysis of the genetic variety and genetic constitution of cashew trees in Boa Vista - Roraima. These results could be utilized in choosing better progenitores among the cashew trees that have already been studied and to start a programme for the betterment of fruit quality, once these the natural resources show economic potentiality.